Rice yields and soil nutrients response to liming method and dosages in field cultivation - Zhou, Jiang-Ming (Penerbit Universiti Kebangsaan Malaysia, 2022)
It is important to develop a new convenient and environmentally-friendly technology of liming for sustainable rice production on acidic soil area. Thus, an experiment was conducted to evaluate the effect of application methods and rate of lime on soil properties and rice yield. The results showed that a similar ameliorating effect on agricultural acidic soil were found between massive quicklime and powered hydrated lime. Interestingly, optimized application rate of lime significantly increases rice yield, while over-liming leads to an adverse effect to the rice production. The changes of soil nutrients affected by liming rates were related to organic matter content and soil texture, with elevated mineralization of organic matter were found in organic and sandy soil. Conclusively, massive quicklime method has been found to be optimal for rice cultivation on acidic soil conditions with rates of 1500-2250 kg/ha for clay soil and 2250-3000 kg/ha for sandy soil, respectively.